Using pressure and support to create a qualified workforce. - Ryan, Sharon; Ackerman, Debra J. (Education Policy Analysis Archives, 2005)
In order for any new initiative to be implemented, it is generally assumed that policy actors need both motivation to comply with a new initiative and adequate assistance to implement the required change successfully. The study reported here examined the impact of a system of pressure and supports created to encourage preschool teachers working in public school, Head Start, and child care settings to obtain a teaching credential by a court imposed deadline. Findings from the sample of 689 teachers indicate that the court mandate, in combination with a scholarship program and an accessible number of certification programs, motivated many preschool teachers to improve their qualifications. Paradoxically, it was also found that the mandate may contribute to a depletion of the workforce if teachers who obtain a qualification move out of preschool into higher status positions. Findings of this study suggest that policymakers should consider systems of pressure and support not only to achieve short term goals, but to maintain outcomes over the long term, as well.